A case study in non-inferiority margin selection in a two-arm trial - Liang, Xiao (Kansas State University, 2017)
Non-inferiority trials have been widely used in many medical areas. The goal of a non-inferiority trial is to show that a new test therapy is either better or not too much worse than the active control rather than showing the test therapy is superior to a negative control (i.e. placebo). The appeal of a non-inferiority trial is that it is often unethical to give some patients a treatment with no therapeutic benefit. When designing a non-inferiority trial, the issues of assay sensitivity, sample size, constancy condition, and a suitable non-inferiority margin need to be considered. A poor choice of the non-inferiority margin is a major reason that many non-inferiority trials fail. A numerical example is presented to show how to estimate the non-inferiority margin without historical data.
Keywords: non-inferiority trial; non-inferiority margin; superiority margin